2010
DOI: 10.1017/s002966511000011x
|View full text |Cite
|
Sign up to set email alerts
|

Treating irritable bowel syndrome with probiotics: the evidence

Abstract: Irritable bowel syndrome (IBS) is a disorder of chronic abdominal pain, altered bowel habit and abdominal distension. It is the commonest cause of referral to gastroenterologists in the developed world and yet current therapeutic strategies are often unsatisfactory. There is now increasing evidence linking alterations in the gastrointestinal (GI) microbiota and IBS. Changes in faecal and mucosa-associated microbiota, post-infectious IBS, a link with small intestinal bacterial overgrowth and an up-regulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
6

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 75 publications
(141 reference statements)
1
31
0
6
Order By: Relevance
“…(3) IBS symptoms can be improved by treatments that target the microbiota (antibiotics, probiotics, prebiotics). This aspect has also been recently reviewed (Moayyedi et al, 2010;Parkes et al, 2010;Pimentel & Lezcano, 2007) and will not be further discussed in this review.…”
Section: Current Conceptions Of the Intestinal Microbiota In Ibsmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) IBS symptoms can be improved by treatments that target the microbiota (antibiotics, probiotics, prebiotics). This aspect has also been recently reviewed (Moayyedi et al, 2010;Parkes et al, 2010;Pimentel & Lezcano, 2007) and will not be further discussed in this review.…”
Section: Current Conceptions Of the Intestinal Microbiota In Ibsmentioning
confidence: 99%
“…(3) IBS symptoms can be improved by treatments that target the microbiota (antibiotics, probiotics, prebiotics). This aspect has also been recently reviewed (Moayyedi et al, 2010;Parkes et al, 2010;Pimentel & Lezcano, 2007) and will not be further discussed in this review.The differences in the intestinal microbiota between IBS patients and healthy controls (HCs) have mostly been studied using faecal material, as this is the most accessible source of the GI microbiota. For clarity and easier comparability of the results, we first discuss the results in which IBS patients were not subdivided according to Rome II criteria but were compared as a single group with the HCs.…”
mentioning
confidence: 99%
“…The therapeutic effect of probiotics varied in different studies for different strains chosen and trial designs. But a meta-analysis of these studies confirmed the benefit of probiotics in the treatment of IBS 114. However, probiotics cannot be effective for all IBS patients, so further work is deserved to identify the patient groups which can get most benefit from it and to choose the most appropriate and effective strains.…”
Section: Introductionmentioning
confidence: 99%
“…Mantenimiento de la microbiota intestinal normal: La microbiota intestinal está influenciada por la edad, dieta, condición socio-económica, uso de antibióticos y estado de salud (Parkes et al, 2009). Los probióticos interactúan con la microbiota intestinal y con los receptores de la pared intestinal produciendo variedad de efectos en el hospedador (S. Salminen et al, 2010).…”
Section: Efectos Beneficiosos De Los Probióticosunclassified
“…Los probióticos interactúan con la microbiota intestinal y con los receptores de la pared intestinal produciendo variedad de efectos en el hospedador (S. Salminen et al, 2010). Sin embargo, se desconoce el papel metabólico e inmunológico de la microbiota del tracto gastrointestinal y si estos cambios son primarios o secundarios (Parkes et al, 2009).…”
Section: Efectos Beneficiosos De Los Probióticosunclassified